2023
DOI: 10.3390/foods12214021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Toxigenic Potential of Bacillus cereus sensu lato Isolated from Raw Berries and Their Products

Márcia Oliveira,
Marta Carvalho,
Paula Teixeira

Abstract: Bacillus cereus is estimated to be responsible for 1.4–12% of all food poisoning outbreaks worldwide. The objective of this study was to investigate the toxigenic potential of 181 isolates of B. cereus previously recovered from different types of berries and berry products (strawberries, raspberries, blackberries, and blueberries) by assessing the presence of enterotoxin genes (hblA, hblC, hblD, nheA, nheB, nheC, and cytK) and an emetic toxin cereulide synthetase gene (ces). The cytotoxic activity on Caco-2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…According to estimates from the World Health Organization in 2021, approximately 600 million people worldwide suffer from foodborne diseases each year, resulting in around 420,000 deaths. B. cereus is implicated in 1.4% to 12% of all global food poisoning incidents [ 2 ]. A study conducted by the State Key Laboratory of Applied Microbiology Southern China revealed that about 27% of samples from pasteurized milk, even after undergoing pasteurization, were contaminated with B. cereus [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to estimates from the World Health Organization in 2021, approximately 600 million people worldwide suffer from foodborne diseases each year, resulting in around 420,000 deaths. B. cereus is implicated in 1.4% to 12% of all global food poisoning incidents [ 2 ]. A study conducted by the State Key Laboratory of Applied Microbiology Southern China revealed that about 27% of samples from pasteurized milk, even after undergoing pasteurization, were contaminated with B. cereus [ 3 ].…”
Section: Introductionmentioning
confidence: 99%